The Influence Of Listen-Read-Discuss (LRD) Strategy Toward Students’ Reading Comprehension (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
The aims of this research are to influence of using the LRD strategy towards students’ reading comprehension, and to find out how do students respond to the use of the LRD strategy as a learning media for students' reading comprehension. This research method is quantitative with a pre-experimental research design type one group pretest-posttest design. The instruments in this study were tests, questionnaires, and observations.. The results showed that there was an influence of toward the LRD strategy on students' reading comprehension. From the results of the paired sample test, a significance value or Sig. (2- tailed) is 0,00 less than 0,05. Based on the criteria for the hypothesis of the paired sample test If the value (p) > Sig (0.05) means that Ha is rejected, and if the value (p) < Sig (0.05) means that Ha is accepted, it is supported by the analysis of paired sample tests by comparing the t-test with the t-table, where t-test > t-table is 18,004 > 2,042 with the criteria if t-test > t-table means Ha is accepted, if t-test < t-table means Ha is rejected. Thus, it can be concluded that the hypothesis in this study is accepted. Students have a significant influence from toward the Listen-Read-Discuss strategy on students' reading comprehension. There is a good response to the LRD strategy. Based on the analysis, it can be concluded that the LRD strategy is an influential learning media to assist students in reading comprehension.